Impact on post-stroke injury: Co-administration of metformin and CoQ10 in cerebral ischemia injury - Avinash Singh Mandloi, Chanda Malviya, Chandrashekhar D. Upasani, Vipin Dhote, Aman B. Upaganlawar (Journal of Applied Pharmaceutical Science, 2024)
Developing effective therapeutics for stroke, extending beyond brain injury to overcome the post stroke complications is the need of hour. Post-stroke recovery is a primary research goal, necessitating treatments targeting multiple aspects of stroke pathology to enhance patient outcomes. Co-administration of therapies presents a promising approach to address post-stroke complications. Here, we assessed the combined effect of Metformin (MET) and Coenzyme Q10 (CoQ10) in mitigating post-stroke injury in rats. Rats underwent bilateral common carotid artery occlusion followed by reperfusion. They were divided into groups: Sham, IR (ischemic reperfusion), MET-treated, CoQ10-treated, and co-administered (MET+CoQ10). All treatments were given intramuscularly for 1–3 days post-stroke. Brain infarct size was significantly reduced in all treatment groups as compared to IR. Neurological score, % alteration, transfer latency, and discrimination ratio are ameliorated in all treatment groups. Coadministration shows a significant reduction in LPO as compared to IR and MET-treated animals. Glutathione and BBB integrity improved in all treated groups. Histology shows less pyknosis and vacuolization in treated rats’ hippocampus. MET and CoQ10 treatment for 3 days post-stroke exhibited neuroprotective effects and improved cognitive function. Co-administration demonstrated enhanced antioxidant defense compared to individual treatments, suggesting potential synergy in mitigating post-stroke complications.
Keywords: Post-stroke injury, metformin, co-enzyme Q10, stroke, oxidative stress, behavioral activity